Studies on separation and properties of lumbrokinase in Pheretima praepinguis - Mei, Tang; Cao, Liu; Zi, Liang; Mingfu, Gong; Die, Hu (Bangladesh Journal of Pharmacology, 2016)
The purpose of this study was to separate lumbrokinase in Pheretima praepinguis and examine its enzymatic properties. With P. praepinguis as material, lumbrokinase was separated with the salting out method. Lumbrokinase activity was measured with casein medium plate method. Effect of pH and temperature on lumbrokinase activity was studied. Results of lumbrokinase separated from P. praepinguis was relatively high. Lumbrokinase activity in neutral or slightly alkaline environment was higher. Lumbrokinase had tolerance ability to high temperature, with highly enzymatic activity under 60°C and wide range of temperature adaptation.